Black power in the suburbs : the myth or reality of African-American suburban political incorporation - Johnson, Valerie C. (SUNY series in African American studies., 2002)
"The country's largest concentration of African American suburban affluence represents a unique laboratory to study the internal factors associated with African American political ascendancy and the convergence of race and class. Black Power in the Suburbs chronicles Prince George's County, Maryland, and the twenty-three year quest by African Americans to influence educational policy and become equal partners in the county's governing coalition. Johnson challenges conventional notions of a monolithic community by addressing the manner in which class cleavages among African Americans affect their representation and policy interests in suburbia. She also documents white resistance to power sharing and the impact of school desegregation on white population trends."--Jacket